Photoprotection mechanisms in Quercus ilex under contrasting climatic conditions - Camarero, Jesús Julio; Olano, José Miguel; Arroyo Alfaro, Sandra Jackeline; Fernández-Marín, Beatriz; Becerril, José Maria; García-Plazaola, José Ignacio (Flora - Morphology, Distribution, Functional Ecology of Plants, 2012)
Acclimation to local conditions may produce adaptive responses in plants subjected to diverse climatic stresses. However, it has not been assessed how local adaptation and phenotypic plasticity contribute to photoprotection mechanisms in response to contrasting climatic conditions in Mediterranean tree species. We analyzed photoprotectionmechanisms inmature trees oftheMediterranean evergreen oak Quercus ilex at three sites with contrasting climatic conditions, i.e. xeric, continental and mesic sites. We studied morphological and physiological parameters indicative of photoprotection in adult trees in the ﬁeld. In order to establish whether these parameters were genetically determined we compared adults with seedlings germinated from acorns of the three sites and grown under common greenhouse conditions. In the ﬁeld we found no signiﬁcant differences in most of the physiological parameters in summer, but in winter the adulttrees fromthe continental site were photoinhibited. In contrast,there were signiﬁcant differences between seedlings in most photoprotective parameters evaluated. Morphological traits such as trichome density and leaf reﬂectance differed between populations, both in ﬁeld-grown trees and in greenhouse-grown seedlings, being higher in all cases in plants from the xeric site than elsewhere. Our ﬁndings suggest the existence of constitutive differences in leaf photoprotection mechanisms among Q. ilex populations. These divergences may represent an inherent source for more stress tolerant ecotypes in the face of changing climatic conditions.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: ecotypes; Holm oak; Mediterranean; photoprotection; Trichomes

Photoprotective responses of Mediterranean and Atlantic trees to the extreme heat-wave of summer 2003 in Southwestern Europe - García-Plazaola, José Ignacio; Esteban, Raquel; Hormaetxe, Koldobika; Fernández-Marín, Beatriz; Becerril, José Maria (Trees, 2008)
Summer 2003 was extremely hot in Europe. High light in combination with heat and drought exacerbates the generation of photo-oxidative stress. Under these conditions photoprotective responses can be critical for plant survival. Photoprotection was analysed in 2003 in several Mediterranean and Atlantic woody species. These data were compared with previous summers (1998, 1999 and 2001) to evaluate the potential acclimation for each species. A pattern of changes consisting on a decrease in chlorophyll, ascorbate and Fv/Fm and an increase in tocopherol, xanthophyll cycle pigments (VAZ) and deepoxidation index was regularly observed. Acclimation potential was measured by the use of the plasticity index for each parameter. Mediterranean species were more plastic than Atlantic ones. The latter were unable to increase antioxidant pools to the same extent or to downregulate the efﬁciency of light energy conversion. These results indicate that most Mediterranean species are able to perform an efﬁcient acclimation to heat stress, whilst Atlantic species will be more affected by climate warming.
Keywords: á summer 2003; antioxidants; antioxidants á heat-wave á; heat-wave; mediterranean species; mediterranean species á photoprotection; photoprotection; summer 2003

Photoprotective responses of Mediterranean and Atlantic trees to the extreme heat-wave of summer 2003 in Southwestern Europe (Trees, 2008)
Summer 2003 was extremely hot in Europe. High light in combination with heat and drought exacerbates the generation of photo-oxidative stress. Under these conditions photoprotective responses can be critical for plant survival. Photoprotection was analysed in 2003 in several Mediterranean and Atlantic woody species. These data were compared with previous summers (1998, 1999 and 2001) to evaluate the potential acclimation for each species. A pattern of changes consisting on a decrease in chlorophyll, ascorbate and Fv/Fm and an increase in tocopherol, xanthophyll cycle pigments (VAZ) and deepoxidation index was regularly observed. Acclimation potential was measured by the use of the plasticity index for each parameter. Mediterranean species were more plastic than Atlantic ones. The latter were unable to increase antioxidant pools to the same extent or to downregulate the efﬁciency of light energy conversion. These results indicate that most Mediterranean species are able to perform an efﬁcient acclimation to heat stress, whilst Atlantic species will be more affected by climate warming.